Elastic-plastic stress analysis of shrink-fitted thick FGM cylinders - Zrinej Samiha; Laghzale Nor-Eddine; Bouzid Abdel-Hakim A. (FME Transactions)
This paper addresses the stress analysis of shrink-fitted thick-walled cylinders made of functionally graded material (FGM). Analytical solutions are provided for the elastic-plastic behavior of shrink-fitted axisymmetric thick-walled FGM cylinders based on the linear plane elasticity theory and plasticity laws. Due to the material's functional gradation, mechanical characteristics like Young's modulus, yield stress, and plastic parameters are controlled by a power function along the wall thickness. Considering a plane strain case, elastic-perfectly plastic model and Von Mises yield criterion; theoretical solutions are obtained for both elastic and plastic phases. The radial, hoop, axial, and equivalent Von Mises stresses are obtained for up to 25%, 50%, and 75% of cylinder plasticization for the elastic and plastic zones. Stresses are given in terms of interference and geometrical and mechanical parameters of the assembly. In addition, the interferences to start plastic deformation and the full plastic collapse of the cylinder are discussed. Moreover, the effect of the gradient index on the contact pressure and both the start of yield and plastic collapse pressures are conducted. The analytical results found in the current research are compared with the numerical solutions carried out by Ansys Workbench. Both results show a good agreement.